2012
DOI: 10.3746/jkfn.2012.41.11.1546
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Sorghum Tea according to Milling Type and Pan-fried Time

Abstract: In this study, sorghum teas were prepared from Sorghum bicolor L. Moench subjected to different types of milling (no milling (0%), minimum milling (5%), and milling (20%)) and pan-firing times (1 to 10 minutes), and its quality characteristics were investigated. With regards to milling type, total polyphenolic, flavonoid, tannin contents, and antioxidant activities of ethanol extracts from both no milling sorghum and its tea were highest, followed by minimum milling and milling in decreasing order. Crude nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…It is reported that phenolic compounds stabilize DPPH and ABTS radicals (Ji & Kim, ), which may be associated with the similar patterns between TPCs and DPPH and ABTS outcomes. Moreover, both DPPH and ABTS initially increased and then decreased, which is in agreement with a study by Ko et al () that reported antioxidant ability of sorghum tea upon roasting. Also, Suh and Chun () investigated the antioxidant ability of barley upon roasting and the result showed a similar pattern of decreasing both antioxidant ability and TPCs during roasting.…”
Section: Resultssupporting
confidence: 92%
“…It is reported that phenolic compounds stabilize DPPH and ABTS radicals (Ji & Kim, ), which may be associated with the similar patterns between TPCs and DPPH and ABTS outcomes. Moreover, both DPPH and ABTS initially increased and then decreased, which is in agreement with a study by Ko et al () that reported antioxidant ability of sorghum tea upon roasting. Also, Suh and Chun () investigated the antioxidant ability of barley upon roasting and the result showed a similar pattern of decreasing both antioxidant ability and TPCs during roasting.…”
Section: Resultssupporting
confidence: 92%